Contribution of policy change on maize varietal development and yields in Kenya. Issue 1 (14th May 2019) - Nagarajan, Latha; Naseem, Anwar; Pray, Carl
Abstract : Purpose: Since the start of seed and other market reforms in the 1990s, the annual number of improved varietal releases for maize in Kenya has increased substantially. Prior to the reforms, private firms were restricted in introducing new varieties, could not protect their intellectual property and farmers had to rely exclusively on improved seeds developed and marketed by the public sector. Reforms have resulted in not only private firms entering the market and releasing improved varieties, but also an increase in varietal releases by the public sector. The purpose of this paper is to review some of the key policy reforms related to maize in Kenya, and their impacts on varietal development and yields. Design/methodology/approach: The authors estimate a yield model that relates national maize yields to a number of input policy variables. The authors employ a two-stage least square regression, as one of the explanatory variables – the number of varietal releases – is likely endogenous with yield. The authors use policy variables such as public R&D, the number of plant breeder's rights issued, and the years since private varieties have been introduced as instrument variables to estimate their influence new varietal releases directly, and then new varieties, inputs and other policies to measure their impact on yields. Findings: The results show that policy changes such as the introduction of intellectual property rights had an important impact on the number of improved maize varieties released. However, the outcomes of the policy change such as the number of varieties and the share of area under improved varieties has no impact on increasing maize yields. The authors argue that this is because farmers continue to use older improved varieties because of the dominance of a parastatal in the maize, seed market and that newer improved varieties may not have the assumed yield advantage. Future policy and programs should be directed toward increasing the adoption of improved varieties rather than simply releasing them. Originality/value: This paper provides evidence that while policy change may lead to new varietal development and release, its aggregate productivity impacts may be limited without additional reforms and intervention.